KETERKAITAN DARI TRANSFORMATIONAL LEADERSHIP, WORK ENVIRONMENT, CAREER PLANNING, JOB SATISFACTION, DAN TURNOVER INTENTION - Ericho Agil Nugraha; Sarfilianty Anggiani (POLITEKNIK LP3I JAKARTA, 2022)
The research target is to analyze the impact on turnover intention of transformational leadership, work environment, career planning and job satisfaction. The research method is quantitative with data analysis using factor analysis and structural equation modeling (SEM) with SmartPLS. Respondents' data collection was selected using the purpose sampling method on employees of State-Owned Enterprises (BUMN) engaged in the construction sector as many as 154 respondents. And research findings are transformational leadership, work environment, career planning and job satisfaction affect turnover intention and transformational leadership, work environment and career planning affect job satisfaction.Keywords - Transformational leadership, work environment, career planning, job satisfaction, turnover intention